Behavior and strength of slender high strength concrete columns - Wong, Foo Yu. (2009)
The objective of this report is to study the behavior and strength of slender high strength concrete (HSC) columns analytically. These columns are pin-ended and subject to short-term eccentric loading about the minor axis. Data has been obtained from the research of Lloyd and Rangan, RH Basappa Setty and BV Rangan, and Jae-Hoon Lee and Hyeok- Soo Son.